Upaya Pencegahan Tindak Pidana Korupsi Melalui Peran Serta Masyarakat - Ridwan Ridwan (Kanun Jurnal Ilmu Hukum, 2014)
Corruption is a crime having an exstraordinary effect. The highest number of the cases is the  the worst threat for people welfare as the financial loss of state meaning that the welfare will be difficult to be achieved. Thus, it is necessary to get people participation in preventing the crime. Despite the fact that the effort would not be successful to eradicate corruption in Indonesia as it is deemed as white collar crime. However, it is important to done because it is kind of social control. The higher participation of the people, the lesser the crime will be. Such effort is a part of government responsibilitu, concretely by realizing the Government Regulation Number 71, 2000 regarding the Code of Conduct of People Participation in Running Governance by rewarding them who enforce the crime. The Efforts of Corruption Prvention Through Community Participation